Issues and Challenges of Video Dissemination in VANET and Routing Protocol: Review - Hammood, Omar A.; M. N. M., Kahar; Mohammed, Muamer N.; Hammood, Waleed A. (Medwell Journals, 2017)
New technology called Vehicular Ad-hoc Networks (VANETs), this topology quick changing and frequent disconnection has taken huge attention within last years and makes it complex to design an active routing protocol to routing data among vehicles, Vehicle to Vehicle (V2V) communication and Vehicle to roadside Infrastructure (V2I). Routing protocols which existing for VANETs don’t efficient upon meet all traffic scenarios. Hence, the study of an efficient routing protocol has received significant recognition. Therefore, it is really essential to distinguish the pros and cons of routing protocols that can be done for additional growth or development of any new routing protocol. This study present different aspects of VANET technologies that form a real life vehicular network. More detail for the potential applications and current initiatives for the vehicle networks are covered. In addition, brief discussion of existing related work on video streaming in VANETs which are focused on different protocol stack layers. Finally, provides a comprehensive background on vehicular communication networks. Also, the surveys different routing techniques that have improved video broadcasting functionality to achieve acceptable QoS over VANETs.